Effects of aging on motor control strategies during bimanual isometric force control. (August 2019) - Jin, Yan; Seong, JiWon; Cho, YoungChae; Yoon, BumChul
Aging-induced degeneration of the neuromuscular system would result in deteriorated complex muscle force coordination and difficulty in executing daily activities that require both hands. The aim of this study was to provide a basic description of how aging and dual-task activity would affect the motor control strategy during bimanual isometric force control in healthy adults. In total, 17 young adults (aged 25.1 ± 2.4 years) and 14 older adults (aged 72.6 ± 3.4 years) participated in the study. The subjects were instructed to press both hands simultaneously to match the 1 Hz sine curve force under two conditions (with or without calculation) with continuous visual feedback. Differences in bimanual motor synergy, bimanual coordination, force accuracy, force variability, and calculation speed were compared. This study found that the specific motor control strategy of older adults involved a decreased bimanual force control ability with both increased V UCM and V ORT, and was not influenced by dual tasking. These findings might have implications for establishing interventions for aging-induced hand force control deficits.